Pengaruh Program Gratis Ongkos Kirim, Live Streaming, dan Online Customer Review Terhadap Keputusan Pembelian pada Platform E- Commerce Tiktok Shop - Florida Mandiriani Suwaji; Totok Haryanto; Wida Purwidianti; Arini Hidayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of the free shipping program (X1), live streaming (X2), and online customer reviews (X3) on purchasing decisions (Y) on the TikTok Shop e-commerce platform. The method used was quantitative by distributing questionnaires filled in by 110 respondents in the Purwokerto area, but only 103 respondents met the criteria. The results of the analysis show that the three variables The validity and reliability test states that the questionnaire instrument used has a good level of validity and reliability. The coefficient of determination test shows that the three X variables are able to contribute 43.1% to variable Y in the TikTok Shop. The research results are consistent with the theory which states that the free shipping program variables (X1), live streaming (X2), and online customer reviews (X3) are important factors that influence the purchasing decision variable (Y).